From lab to mass production: a policy for enabling the licensing of mRNA vaccines - Panagopoulos, Andreas; Sideri, Katerina (Frontiers in Public Health, 2023)
Using the South African vaccine technology transfer hub supported by the WHO as an example, we show that the know-how needed to move mRNA vaccines from prototype to mass-production acts as an invisible barrier to market entry of mRNA vaccines. Overcoming this barrier relies on scarce human capital. In view of this scarcity and in preparation for the next pandemic, we propose broadening the scope of an existing WHO program, the WHO Academy, so that it coordinates knowledge diffusion initiatives by forming a systematized repository of know-how and a register of experts. As we explain, this proposal has an advantage in overcoming barriers to entry over current approaches of know-how acquisition.